Muzejska prodajalna - Šola, Tomislav (Array, 2003)
The museum shop's offer and the atmosphere the visitors encounter upon entering must be as far away from the aggressive approach as possible, while the taste and quality of the material must be appropriate. Many visitors appreciate the calm and relaxed atmosphere in museum shops. We must not forget that here, too, museums must provide proof of their dedication to excellence and social responsibility. The shop should represent a place that offers good value for money.